Kurikulum Bahasa Arab KMA 183 pada Tingkatan Madrasah Aliyah - Muhammad Zikran Adam; Syuhadak; Siti Aliyya Laubaha; Nicky B. Lasanggo (Faculty of Education and Teacher Training, 2024)
In 2019 the Ministry of Religion issued KMA 183 concerning Islamic Education and Arabic Curriculum in madrasas. The aim of developing the curriculum is to answer existing challenges, namely internal and external challenges, internal challenges, namely making Arabic language learning functional and communicative, and external challenges, namely making students able to use Arabic as a means of communication on an international scale. This research aims to analyze whether the Arabic language curriculum at Madrasah Aliyah has answered existing internal and external challenges. The method used by researchers is qualitative, with the type of library research. Data sources were taken from documents related to KMA 183 Arabic language subjects, both from KMA 183 Decisions and scientific articles. The data collection technique uses documentation techniques, then the data analysis is carried out in 3 stages, namely the stages of data collection, data categorization, data analysis, and data presentation. Based on the results of the analysis, curriculum development, and objectives as well as competencies, materials, and themes in the Arabic language curriculum at Madrasah Aliyyah are appropriate and can answer existing challenges.